The chemical composition of a regular halo globular cluster: NGC 5897 - Koch-Hansen, Andreas; McWilliam, Andrew (Astronomy and astrophysics, 2014)
We report for the first time on the chemical composition of the halo cluster NGC 5897 (R⊙ = 12.5 kpc), based on chemical abundance ratios for 27 α-, iron-peak, and neutron-capture elements in seven red giants. From our high-resolution, high signal-to-noise spectra obtained with the Magellan/MIKE spectrograph, we find a mean iron abundance from the neutral species of [Fe/H] = − 2.04 ± 0.01 (stat.) ± 0.15 (sys.), which is more metal-poor than implied by previous photometric and low-resolution spectroscopic studies. The cluster NGC 5897 is α-enhanced (to 0.34 ± 0.01 dex) and shows Fe-peak element ratios typical of other (metal-poor) halo globular clusters (GCs) with no overall, significant abundance spreads in iron or in any other heavy element. Like other GCs, NGC 5897 shows a clear Na-O anti-correlation, where we find a prominent primordial population of stars with enhanced O abundances and approximately solar Na/Fe ratios, while two stars are Na-rich, providing chemical proof of the presence of multiple populations in this cluster. Comparison of the heavy element abundances with the solar-scaled values and the metal-poor GC M15 from the literature confirms that NGC 5897 has experienced little contribution from s-process nucleosynthesis. One star of the first generation stands out in that it shows very low La and Eu abundances. Overall, NGC 5897 is a well behaved GC showing archetypical correlations and element-patterns, with little room for surprises in our data. We suggest that its lower metallicity could explain the unusually long periods of RR Lyr that were found in NGC 5897.
Gesehen am 25.08.2020